PENGEMBANGAN TRAINER PENGATURAN MOTOR LISTRIK TERPROGRAM PADA MATA PELAJARAN INSTALASI MOTOR LISTRIK - Welly Aruan Rosalina Rosalina; Panahatan Sitorus (JEVTE: Journal of Electrical Vocational Teacher Education, 2022)
Abstract Along with the times, the technology around us is always developing. One of the technological developments in question is the existence of a new type of microcontroller produced by Atmel. The microcontroller in question is the Arduino Uno. This type of microcontroller has many advantages when compared to the previous type of microcontroller. The purpose of this development is to simplify the work in regulating electric motors. The research method used in this research is development research or which is known as research and development (R&D). The data collection technique used in this study was a questionnaire containing validation statements. The questionnaires filled out by media experts and practical experts were media validation, trainers and jobsheets. The results of the validity of this media trainer MEET THE REQUIREMENTS seen from the results of the media trainer requirements test by 2 media experts who found the first media expert score was 75% and the second media expert was 90% with an average percentage score of 82.5%. Then the trainer validation found VERY WORTHY results seen from the results of the trainer requirements test by 2 expert practitioners who found the first practitioner expert score was 96.2% and the second practitioner expert was 95%. With an average score percentage of 95.6%. For the requirement test data, it can be concluded that this trainer is VERY WORTHY, seen from the results of the trainer requirements test by 2 expert practitioners who found that the first expert's score was 94.2% and the second practitioner expert was 95.2% with an average percentage score of 94,7%. Keywords: Trainer Development, Microcontroller. AbstrakSeiring dengan  perkembangan zaman, teknologi yang ada di sekitar kita selalu berkembang. Salah satu perkembangan teknologi yang dimaksud yaitu adanya jenis baru mikrokontroler yang diproduksi oleh Atmel. Mikrokontroler yang dimaksud yaitu Arduino Uno. Mikrokontroler jenis ini memiliki banyak kelebihan jika dibandingkan dengan jenis mikrokontroler sebelumnya. Tujuan dari pengembangan ini adalah untuk mempermudah pekerjaan dalam pengaturan motor listrik. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian pengembangan atau yang dikernal dengan research and development (R&D). Teknik pengumpulan data yang dilakukan dalam penelitian ini adalah angket yang berisi pernyataan-pernyataan validasi. Angket yang diisi oleh ahli media dan ahli praktis adalah validasi media, trainer dan jobsheet. Hasil validitas media trainer ini MEMENUHI SYARAT dilihat dari hasil uji persyaratan media trainer oleh 2 orang ahli media yang didapati skor  ahli media pertama sebesar 75% dan ahli media kedua sebesar 90% dengan rata-rata persentase skor sebesar 82,5%.  Lalu validasi trainer di dapati hasil SANGAT LAYAK dilihat dari hasil uji persyaratan trainer oleh 2 orang ahli praktisi yang didapati skor  ahli praktisi pertama sebesar 96,2% dan ahli praktisi kedua sebesar 95%. Dengan rata-rata persentase skor sebesar 95,6%.  Untuk data uji persyaratan dapat disimpulkan bahwasanya trainer ini SANGAT LAYAK dilihat dari hasil uji persyaratan trainer oleh 2 orang ahli praktisi yang didapati skor  ahli praktisi pertama sebesar 94,2% dan ahli praktisi kedua sebesar 95,2% dengan rata-rata persentase skor sebesar 94,7%. Kata Kunci: Pengembangan Trainer, Mikrokontroler